To intervene or not to intervene: intervention before the court of justice of the european union in environmental and migration law. Issue 8 (14th September 2022) - Krommendijk, Jasper; van der Pas, Kris
ABSTRACT: Little is known about the (legal) possibilities and practice of intervention before the Court of Justice of the EU, despite a seeming growth in strategic litigation by NGOs, especially in areas such as migration and the environment. This article fills this gap by looking at the legal framework as well as conducting empirical research. It also compares the practice of intervention before the CJEU with its counterpart in Strasbourg, the European Court of Human Rights. The findings show that intervention before the CJEU is difficult and hence limited. The more welcoming approach of the ECtHR can be a source of inspiration for the CJEU to relax its restrictive approach. The latter is justified on the basis of reducing differences between national procedural rules on intervention as well as the potential of interventions to improve the quality and reasoning of CJEU judgments.